Autoionization dynamics of helium nanodroplets resonantly excited by intense XUV laser pulses. (17th August 2020) - Ovcharenko, Y; LaForge, A C; Langbehn, B; Plekan, O; Cucini, R; Finetti, P; O'Keeffe, P; Iablonskyi, D; Nishiyama, T; Ueda, K; Piseri, P; Di Fraia, M; et al.
Abstract: The ionization dynamics of helium droplets irradiated by intense, femtosecond extreme ultraviolet (XUV) pulses is investigated in detail by photoelectron spectroscopy. Helium droplets are resonantly excited to atomic-like 2p states with a photon energy of 21.5 eV and autoionize by interatomic Coulombic decay (ICD). A complex evolution of the electron spectra as a function of droplet size (250 to 10 6 He atoms per droplet) and XUV intensity (10 9 –10 12 W cm −2 ) is observed, ranging from narrow atomic-like peaks that are due to binary autoionization, to an unstructured feature characteristic of electron emission from a nanoplasma. The experimental results are analyzed and interpreted with the help of a numerical simulation based on rate equations taking into account all relevant processes—multi-step ionization, electronic relaxation, ICD, secondary inelastic collisions, desorption of electronically excited atoms, and collective autoionization (CAI).